Integrated assessment of scale impacts of watershed intervention : assessing hydrogeological and bio-physical influences on livelihoods - Reddy, V. Ratna; Syme, Geoffrey J. (Amsterdam : Elsevier, 2015)
Integrated Assessment of Scale Impacts of Watershed Interventions is the outcome of a multi-disciplinary research team of social scientists, hydrologists (groundwater and surface water), modellers; and bio-physical scientists who have worked together over five years to develop an integrated model of the sustainability of biophysical, economic and social impacts of watersheds. Impacts of watershed interventions are assessed at upstream, mid-stream and downstream locations of two hydrological units that are characterised with differential bio-physical attributes.
Part I. Setting. Introduction / V. Ratna Reddy and Geoffrey J. Syme ; Analytical framework, study design, and methodology / Geoffrey J, Syme, V. Ratna Reddy, Shakeel Ahmed, K.V. Rao, Paul Pevalic, Wendy Merritt and T. Chiranjeevi -- Part II. Hydro-geological and bio-physical aspects of the watersheds. Investigating geophysical and hydrogeological variabilities and their impact on water resources in the context of meso-watersheds / P.D. Sreedevi, S. Sarah, Fakhre Alam, Shakeel Ahmed, S. Chandra and Paul Pavelic ; Application of a simple integrated surface water and groundwater model to assess mesoscale watershed development / Paul Pavelic, Jian Xie, P.D. Sreedevi, Shakeel Ahmed and Daniel Bernet ; Modeling the impact of watershed development on water resources in India / Barry Croke, Peter Cornish and Adlul Islam ; Sustainable watershed development design methodology / K.V. Rao, Pratyusha Kranti, Hamsa Sandeep, P.D. Sreedevi and Shakeel Ahmed -- Part III. Socio-economic and livelihood impacts of watersheds. Assessing livelihood impacts of watersheds at scale: an integrated approach / V. Ratna Reddy, T. Chiranjeevi, Sanjit Kumar Rout and M. Sreenivasa Reddy ; Evaluating the determinants of perceived drought resilience: an empirical analysis of farmers' survival capabilities in drought-prone regions of South India / Ram Ranjan, Deepa Pradhan, V. Ratna Reddy and Geoffrey J. Syme ; Modeling livelihood indicators and household resilience using Bayesian networks / Wendy Merritt, Brendan Patch, V. Ratna Reddy, Sanjit Kumar Rout and Geoffrey J. Syme ; Justice and equity in watershed development in Andhra Pradesh / Geoffrey J. Syme, V. Ratna Reddy and Ram Ranjan -- Part IV. Integrating science into policy and practice. High stakes- engagement with a purpose / T. Chiranjeevi, Geoffrey J. Syme and V. Ratna Reddy ; Exploring implications of climate, land use, and policy intervention scenarios on water resources, livelihoods, and resilience / Wendy Merritt, K.V. Rao, Brendan Patch, V. Ratna Reddy, G. Syme and P.D. Sreedevi ; Summary and conclusion / V. Ratna Reddy and Geoffrey J. Syme.
Includes bibliographical references and index.
Print version record.
Keywords: Watershed management; Watershed management -- Economic aspects; Soil conservation; BUSINESS & ECONOMICS -- Real Estate -- General; Soil conservation; Watershed management; Watershed management -- Economic aspects; Electronic books; Electronic book